1987
DOI: 10.1007/bf00417318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cysteinylphenol, cysteaminylphenol, and related compounds, and in vivo evaluation of antimelanoma effect

Abstract: Phenolic and catecholic compounds were synthesized, by combination with cysteine or cysteamine through thioether bond, and their antimelanoma and melanocytotoxic effects were evaluated. Among nine compounds tested, 4-S-cysteaminylphenol (CAP) resulted in an increase in the life span (% ILS) of melanoma-bearing mice and in the growth inhibition (% GI) of melanoma tissue. 4-S-Cysteinylphenol (CP) and its methyl ester form also showed some increase in % GI. The 2-S-isomers of CP and CAP and diphenolic derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…The methods for synthesis of 4-S-CP and 4-S-CAP were described in our previous report (Miura et al, 1987). NAc-4-S-CAP was also prepared by the method of Padgette et al (1984).…”
Section: Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methods for synthesis of 4-S-CP and 4-S-CAP were described in our previous report (Miura et al, 1987). NAc-4-S-CAP was also prepared by the method of Padgette et al (1984).…”
Section: Chemicalsmentioning
confidence: 99%
“…The details of tumor preparation and growth characteristics were reported in our previous study (Miura et al, 1987). Briefly, excised tumors were homogenized in normal saline.…”
Section: Melanoma Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pursuing our quest further, in this report, we have evaluated the killing effects of 4-S-CAP on B16 melanoma cell lines possessing different melanin-producing activities, and have authors (Dr S. Ito), and the details of this chemical synthesis have been reported previously (Miura et al, 1987). The drug solution was freshly prepared in a Ham's F-10 medium (Gibco, Grand Island, NY) just before use at the beginning of each experiment.…”
mentioning
confidence: 99%
“…Therefore, in a search for more effective melanocytotoxic agents, we have synthesised various phenolic compounds as substrates for tyrosinase, and have demonstrated that, among these synthetic compounds, 4-S-cysteaminylphenol (4-S-CAP) possesses the most significant effect in inhibiting the growth of melanomas in experimental mice (Miura et al, 1987). Pursuing our quest further, in this report, we have evaluated the killing effects of 4-S-CAP on B16 melanoma cell lines possessing different melanin-producing activities, and have authors (Dr S. Ito), and the details of this chemical synthesis have been reported previously (Miura et al, 1987).…”
mentioning
confidence: 99%